Vascular endothelial hyperpermeability induces the clinical symptoms of Clarkson disease (the systemic capillary leak syndrome) - Xie, Zhihui; Ghosh, Chandra C; Patel, Roshni; Iwaki, Shoko; Gaskins, Donna; Nelson, Celeste; Jones, Nina; Greipp, Philip R; Parikh, Samir M; Druey, Kirk M (Blood, 2012)
The systemic capillary leak syndrome (SCLS) is a rare disorder characterized by transient episodes of hypotensive shock and anasarca thought to arise from reversible microvascular barrier dysfunction. Although the high prevalence of a monoclonal gammopathy of unknown significance in SCLS suggests a pathogenic contribution of endogenous immunoglobulins, the mechanisms of vascular hyperpermeability remain obscure. Herein, we report clinical and molecular findings on 23 patients, the largest SCLS case series to date. Application of episodic SCLS sera, but neither the purified immunoglobulin fraction nor sera obtained from patients during remission, to human microvascular endothelial cells caused vascular endothelial cadherin internalization, disruption of interendothelial junctions, actin stress fiber formation, and increased permeability in complementary functional assays without inducing endothelial apoptosis. Intravenous immunoglobulin, one promising therapy for SCLS, mitigated the permeability effects of episodic sera. Consistent with the presence of endogenous, nonimmunoglobulin, circulating permeability factor(s) constrained to SCLS episodes, we found that vascular endothelial growth factor (VEGF) and angiopoietin 2 (Ang2), were elevated in episodic SCLS sera but not in remission sera. Ab-based inhibition of Ang2 counteracted permeability induced by episodic SCLS sera. Comparable experiments with anti-VEGF Ab (bevacizumab) yielded less interpretable results, probably because of endothelial toxicity of VEGF withdrawal. Our results support a model of SCLS pathogenesis in which nonimmunoglobulin humoral factors such as VEGF and Ang2 contribute to transient endothelial contraction, suggesting a molecular mechanism for this highly lethal disorder.